The Urban-Rural Disparities and Associated Factors of Health Care Utilization Among Cancer Patients in China - Wang, Haipeng; Hua, Xingxing; Yao, Nengliang; Zhang, Nan; Wang, Jialin; Anderson, Roger; Sun, Xiaojie (Frontiers in Public Health, 2022)
Objective: This study aimed to examine the urban-rural disparities and associated factors of health care utilization among cancer patients in China. Methods: This study used the data collected from a cross-sectional survey conducted in China. A total of 1570 cancer survivors from three urban districts and five rural counties were selected by using a multistage stratified random sampling method. We measured health care utilization with the way of cancer diagnosis, the number of hospitals visited, and receiving alternative therapies. Chi-square test was used to examine the differences between urban and rural cancer patients. Binary logistic regression analysis was performed to explore the determinants of health care utilization. Results: Among 1570 participants, 84.1% were diagnosed with cancer after developing symptoms, 55.6% had visited two and above hospitals, and 5.7% had received alternative therapies. Compared with urban cancer patients, rural ones were more likely to be diagnosed with cancer after developing symptoms (χ2 =40.04, p<0.001), while they were less likely to visit more than one hospital (χ2 =27.14, p<0.001). Residence area (urban/rural), health insurance type, household income, age at diagnosis, tumor site, stage of tumor, and survival years were significantly associated with health care utilization of cancer patients (p<0.01). Conclusions: Health care utilization was suboptimal among cancers patients in China. Rural cancer patients had less health care utilization including screenings and treatments than urban ones. Policymakers should implement specific strategies to ensure equitable utilization of cancer care. More attention should be paid to the disadvantaged groups and rural cancer patients. Prioritizing health resources allocation is needed to prevent, screen, and treat cancers in rural areas.